OPTIMIZATION OF STEPPER MOTOR CONTROL IN VARIOUS OPERATING MODES - O. I. Laktionov; A. S. Yanko (Автоматизация технологических и бизнес-процессов)
Abstract. The article investigates the topical issue of increasing the efficiency of stepper motor control, which are key elements in positioning systems within robotic platforms. The possibilities of using three popular controllers are considered and compared: Jetson Nano, ESP32 (as affordable solutions for basic control), and Raspberry Pi 5 (for more complex scenarios due to higher computing power and expanded interfaces).